ANALISIS BENTUK DAN RAGAM HIAS KERAMIK PADA SITUS GUA TENGKORAK LALOWATU DI DESA LAWOLATU KECAMATAN NGAPA KABUPATEN KOLAKA UTARA - Syawaluddin Eka Putra; Abdul Alim; Ainussalbi Al Ikhsan (SANGIA: Jurnal Penelitian Arkeologi, 2024)
The Lalowatu Skull Cave site is a burial cave site that has various archaeological remains, which can still be found today, namely ceramic fragments. This research was motivated by the discovery of ceramic fragments found at the Lalowatu Skull Cave site based on their shapes and decorative motifs. So, the problem raised in this research is the shapes and decorative motifs on ceramic fragments found at the Lalowatu Tengkorak Cave site. The aim of this research is to determine the shapes and motifs of the decorative ceramic fragments at the site. This research uses qualitative methods with an inductive reasoning model. The data collection stage was achieved through observation, literature study, interviews and documentation. In analysing the data in this study, morphological analysis (shape) and stylistic analysis (decoration) were used. Based on the research results, the ceramic fragments at the Lalowatu Skull Cave site that have been reconstructed total 19 fragments consisting of 2 types of containers, namely plates and bowls. From the results of the reconstruction of these fragments, they consist of 11 plates and 8 bowls. Meanwhile, there are only 15 ceramic fragments that have decorative motifs, and the other 4 fragments have no motif. Overall, the ceramic fragments have floral and geometric motifs. The decorative motifs on ceramic fragments on average consist of a single decorative motif with a total of 10 fragments and a combined decorative motif with a total of 5 fragments.